A damage plasticity constitutive model for wavy CNT nanocomposites by incremental Mori-Tanaka approach. (15th February 2021) - Yun, Gun Jin; Zhu, Fei-Yan; Lim, Hyoung Jun; Choi, Hoil
Abstract: In this paper, a novel nonlinear micromechanics constitutive model is proposed to simulate elastoplastic and ductile damage behavior for wavy carbon nanotube (CNT) nanocomposites. A modified Eshelby tensor corresponding to wavy CNT is derived by integrating a rotational transformation of the effective composite stiffness tensor along the sinusoidal wavy CNT. The modified Eshelby tensor was utilized to update local and global strain concentration tensors, rebalancing local strains of inclusions and matrix caused by constantly changing algorithmic tangent operator of the matrix. They were integrated with a general framework for nonlinear MT homogenization. A 3D FE micromechanics model is developed to verify the feasibility and accuracy of the proposed model. Following the verification, effects of CNT waviness are closely investigated under various volume fractions, aspect ratios and loading directions.